A multi-operators co-construction site plan of high-speed rail by Chinatower - Xing WANG; Wen QIN; Shuangbo ZHOU; Tao WANG (Dianxin kexue)
With high speed,high penetration losses,multiple networks and multi-standard coverage levels,site plan is the key point of multi-operators coverage of high-speed rail.A multi-operators co-construction site plan by Chinatower was proposed by analyzing the limited coverage networks of operators,comparing overlapping switch area settings of various systems and investigating penetration losses of various trains.